Emission limits and emission allocation schemes in intermodal freight transportation. (September 2020) - Heinold, Arne; Meisel, Frank
Highlights: Orders with given emission limits are routed through an intermodal network. Emission limits impact the selection of allocation schemes and the orders' routing. Emissions allocated to an order can increase if other orders have tight limits. Emission-minimizing solutions often use a mix of allocation schemes in the network. Abstract: The problem addressed in this paper seeks for an optimal routing of freight orders through an intermodal transportation network. We consider the case of environmentally aware customers that request to ship orders with no more than a specified amount of greenhouse gases, which establishes so-called emission limits. In order to ensure that a routing plan complies with each order's emission limit, it is necessary to estimate emissions caused by the used transport services and to allocate these emissions to the orders. We model this problem under cost-, emission- and service-objectives and apply it to an intermodal rail/road network in Europe.